Perkembangan Sosial Emosional Dalam Pelaksanaan Pembelajaran Di Rumah Pada Masa Covid-19 - Dian Indah Sri Lestari; I Wayan Karta; Fahruddin Fahruddin; Baik Nilawati Astini (Indonesian Publication Center, 2021)
This research was motivated by the Covid-19 Pandemic which requires learning from home. The purpose of this study was to find out how the social emotional development ofchildren during the implementation of learning from home during the Covid-19 pandemic in Presak Baru Hamlet, Menemeng Village, Pringgarata District, Central Lombok. This research is a qualitative research with a case study approach. The subjects of this study were children aged 5-6 years as many as 5 children. Data were collected through observation, interviews and documentation. The data analysis used is descriptive qualitative analysis.The result showed that from the 5 children studied there was 1 child who was BSB (Developing Very Well) and 4 other children in the BSH category (Developing According to Expectations). During the pandemic, parents have different ways of developing their children’s social and emotional aspects, such as: inviting them to do daily routines, inviting them to study together, and inviting gymnastics and singing. So, it can be concluded that the social emotional development of children during learning at home during the Covid-19 period in Presak Baru Hamlet, and of course parents and teachers have an important role during the learning process from home.